2015
DOI: 10.1016/j.laa.2015.04.011
|View full text |Cite|
|
Sign up to set email alerts
|

Compatible pairs of commuting isometries

Abstract: The paper is devoted to pairs of commuting isometries. A unique decomposition of such pairs into a compatible and a completely non-compatible part is constructed. The compatible part is fully described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…The functional model for compatible pairs of isometries was given in [14], while a more general geometrical one is given in [8]. Let us recall some results from [8].…”
Section: Compatible Pairsmentioning
confidence: 99%
See 4 more Smart Citations
“…The functional model for compatible pairs of isometries was given in [14], while a more general geometrical one is given in [8]. Let us recall some results from [8].…”
Section: Compatible Pairsmentioning
confidence: 99%
“…Since the model for doubly commuting pairs of isometries is known, it is enough to construct a model for completely non-doubly commuting, compatible pairs. In [8] it is shown that such pairs can be decomposed into two types: pairs defined by a diagram and generalized powers.…”
Section: Compatible Pairsmentioning
confidence: 99%
See 3 more Smart Citations